Legal protection for interested parties in land sale and purchase deeds made by land deed officials who have died - Nafiah, Ulin; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Land plays a fundamental role in human life and is a vital resource. The transfer of land rights, as a legal act, must be legally executed through an authentic deed drawn up before a Land Deed Official (PPAT). This authentic deed serves as strong evidence that guarantees legal certainty and protection for the parties involved in the transaction. However, problems arise when the PPAT who has drawn up the land sale and purchase deed dies before the administrative process or deed settlement is fully completed. This phenomenon creates a legal vacuum and potential vulnerability for interested parties in obtaining adequate legal protection. This study aims to analyze the forms of legal protection for interested parties in land sale and purchase deeds drawn up by deceased PPATs and examine regulations related to the responsibilities of the deceased PPAT's heirs. This study employed a normative juridical legal research method with a statute approach and a conceptual approach. Primary data sources included laws and regulations related to the position of PPAT and the Civil Code, while secondary data were obtained from legal literature, journals, and scientific works. Data analysis was conducted qualitatively by examining applicable regulations, doctrines, and theories of legal protection and legal certainty. The research findings indicate that regulations regarding Land Deed Officials (PPAT) who die and leave unfinished work, particularly regarding authentic deeds, are still less comprehensive than those for Notaries. A deceased PPAT requires his or her heirs to report and submit the PPAT protocol to a successor PPAT appointed by the National Land Agency. However, the lack of norms regarding the completion of unfinished deeds and the authority of the heirs in this regard creates legal uncertainty. Preventive legal protection for PPAT service users is realized through the preparation of valid authentic deeds, the provision of information, maximum service, and comprehensive legal protection. However, when a PPAT dies, this preventative protection is hampered. Repressive or reparative legal protection becomes crucial, including the submission of the protocol and the completion of the deed by the successor PPAT. Heirs have a moral and legal responsibility to facilitate this process, but lack the authority to prepare authentic deeds. The absence of clear sanctions for heirs who fail to submit the protocol is also problematic. Regulatory harmonization is needed to provide legal certainty and optimal protection for all parties.